Research on the Dynamic Response of Gravity Dam under Blasting Vibration. Issue 1 (1st January 2022) - Zhuang, Jinzhao; Li, Chang; Zhang, Bingzhe; Ren, Yanlong; Lü, Mingzhe
Abstract: With the continuous development of blasting technology, it has been widely used in various construction projects. While bringing convenience to construction, it also has a series of negative effects on surrounding buildings (structures), especially the negative effects of blasting vibration on buildings (structures), which has been paid close attention by scholars at home and abroad. For blasting vibration on the dynamic response of the gravity dam to produce, this article adopts the method of numerical simulation, the finite element software ANSYS is applied, the numerical calculation model of concrete gravity dam is established and the dynamic time-history analysis is calculated, in the different blasting conditions, the blasting vibration on the dynamic response of gravity dam is obtained, the calculation and analysis results as basis is supplied for the selection of the blasting vibration monitoring part of the gravity dam.